2021
DOI: 10.1371/journal.pone.0246494
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant women’s daily patterns of well-being before and during the COVID-19 pandemic in Finland: Longitudinal monitoring through smartwatch technology

Abstract: Background Technology enables the continuous monitoring of personal health parameter data during pregnancy regardless of the disruption of normal daily life patterns. Our research group has established a project investigating the usefulness of an Internet of Things–based system and smartwatch technology for monitoring women during pregnancy to explore variations in stress, physical activity and sleep. The aim of this study was to examine daily patterns of well-being in pregnant women before and during the nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 31 publications
(28 reference statements)
1
41
0
Order By: Relevance
“…Hannakaisa Niela-Vile ´ n et al reported heart rate variations, physical activity (step count), and life pressure changes (sleep duration) for known pregnant women during the COVID-19 outbreak in Finland and used a smartwatch to track all parameters. The feasibility of this approach to [ 30 ] is confirmed. Since the epidemic of COVID-19, the obstetric clinic of the Erwin Medical Center of Columbia University has begun to transform the maternity examination into a telemedicine mode.…”
Section: Clinical Application Of Smart Medical Service In Female Pregnancymentioning
confidence: 73%
See 1 more Smart Citation
“…Hannakaisa Niela-Vile ´ n et al reported heart rate variations, physical activity (step count), and life pressure changes (sleep duration) for known pregnant women during the COVID-19 outbreak in Finland and used a smartwatch to track all parameters. The feasibility of this approach to [ 30 ] is confirmed. Since the epidemic of COVID-19, the obstetric clinic of the Erwin Medical Center of Columbia University has begun to transform the maternity examination into a telemedicine mode.…”
Section: Clinical Application Of Smart Medical Service In Female Pregnancymentioning
confidence: 73%
“…These factors can contribute to the proper prolongation of gestational weeks, greatly reducing the premature birth rate, disability rate, and mortality rate of the fetus and greatly increasing the survival rate of pregnant women. This is of great significance to improve the quality of health care during pregnancy and promotes medical development in remote areas [ 28 , 30 , 32 ]. With the popularity of intelligent medical technology, any abnormal situation in pregnant women can be dealt with in time through intelligent medical care.…”
Section: Clinical Application Of Smart Medical Service In Female Pregnancymentioning
confidence: 99%
“…In a parallel study in the US, pregnant women who were engaged in more positive health behaviors were also found to have less anxiety symptoms [34]. A Finnish study monitoring pregnant women's daily patterns of heart rate variability, physical activity and sleep data showed that these variables were associated with coping better with pandemic-related restrictions [70]. Therefore, improving women's social support networks and encouraging socially distant healthy activities, such as online fitness classes suitable for pregnant women, may be targets for enhancing resilience to depression among pregnant women during the pandemic.…”
Section: Discussionmentioning
confidence: 97%
“…For example, to solve the problem that the detection accuracy of a smart bracelet is not high enough, researchers have suggested that a patient must continue to record any symptom accompanied with the detection data of the smart bracelet to conduct a comprehensive judgment using special algorithms [49]. Similarly, a number of studies [50][51][52] also recommended combining smartwatch detection results with self-reported symptoms to determine whether an individual has COVID-19 after symptoms appear.…”
Section: Possible Developments In Smart Technology Applications To Support Mobile Healthcare After the Covid-19 Pandemicmentioning
confidence: 99%